Optimizing Employee Performance through Spiritual and Emotional Intelligence - Didi Putra; Juarsa Badri (CAKRAWALA : Management Science Journal, 2026)
Employee performance in higher education institutions is increasingly recognized as a multidimensional construct influenced not only by technical competence but also by psychological and spiritual dimensions. This study examines the effect of spiritual intelligence and emotional intelligence on employee performance at the Faculty of Cultural Sciences, Universitas Andalas. Employing a quantitative associative approach with multiple linear regression analysis, data were collected from 40 employees using total sampling. Instrument validity was confirmed through Pearson Correlation (r-table = 0.312) and reliability through Cronbach's Alpha (α ≥ 0.60). Classical assumption tests confirmed normality (Asymp. Sig. = 0.133 > 0.05), absence of heteroscedasticity, and absence of multicollinearity (VIF = 1.387). Results demonstrate that spiritual intelligence positively and significantly affects employee performance (β = 0.460; t = 2.208; p = 0.034 < 0.05), and emotional intelligence positively and significantly affects employee performance (β = 0.592; t = 2.777; p = 0.009 < 0.05). The coefficient of determination (R² = 0.417) indicates that both variables explain 41.7% of the variance in employee performance. This study contributes empirical evidence from a non-profit public higher education context in Indonesia, an underexplored institutional environment in existing literature, underscoring the need for spirituality- and emotion-based human resource development strategies in academic institutions.